A kinetic model for 2, 4-dichlorophenol adsorption and hydrodechlorination over a palladized biofilm. (1st May 2022) - Wu, Chengyang; Zhou, Luman; Zhou, Chen; Zhou, Yun; Zhou, Jingzhou; Xia, Siqing; Rittmann, Bruce E.
Highlights: Coupling Pd 0 NPs with the biofilm promoted the adsorption of 2, 4-DCP. The increased local concentration of 2, 4-DCP accelerated HDC in Pd 0 -biofilm. A model simulated well the overall kinetics of 2, 4-DCP removal over Pd 0 -biofilm. Pd 0 -biofilm reinforced thorough 2, 4-DCP removal despite its low concentration. Abstract: Adsorption and catalytic hydrodechlorination (HDC) of aqueous 2, 4-DCP by palladium nanoparticles (Pd 0 NPs) associated with a biofilm (i.e., a Pd 0 -biofilm) was investigated in terms of the removal efficiency of 2, 4-DCP, dechlorinated product selectivity, and reduction kinetics. Experiments were executed with Pd 0 -biofilm and with abiotic Pd 0 NPs-film alone. The 2, 4-DCP-adsorption capacity of Pd 0 -biofilm was 2- to 5-fold greater than that of abiotic Pd 0 NPs-film, and the adsorption accelerated dechlorination by Pd 0 -biofilm, including selectivity to phenol instead of mono-chlorophenols. A mechanistic kinetic model was developed to represent the sequential adsorption and reduction processes. Modeling results represented well the removal of 2, 4-DCP and quantified that Pd 0 -biofilm had a strong affinity for adsorbing 2, 4-DCP. The strong adsorption increased the volume-averaged concentration of 2, 4-DCP concentration inside the Pd 0 -biofilm, compared to the concentration in the bulk liquid. This increase in the local concentration of 2, 4-DCP led to a 2- to 4-fold increase in the reduction rate of 2, 4-DCP in Pd 0 -biofilm, compared to abiotic Pd 0 NPs-film. Thus, coupling Pd 0 NPs with the biofilm promoted 2, 4-DCP removal and full dechlorination despite its low concentration in bulk water. Graphical abstract: Image, graphical abstract